2012
DOI: 10.3800/pbr.7.55
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Aulacoseira ambigua abundance and filament length: biogeochemical implications

Abstract: Aulacoseira ambigua abundance and filament length were measured weekly during spring and autumn bloom periods in Trout Lake, Wisconsin, USA. In addition, several chemical and biological variables thought to influence A. ambigua growth were assessed. Results of the field-based observations were complimented with controlled laboratory experiments to evaluate the effects of phosphorus availability on A. ambigua growth. Relative to the autumn bloom period, A. ambigua colonies were generally larger and more abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In the modern Lake Taupo sediment, this ratio is 16.7, suggesting relatively long filaments of about 17 cells (Table 2). This is analogous to the warm season filament length (11-17 cells) documented by Poister et al (2012) in a Wisconsin lake. Long filaments suggest relatively calm waters and nutrient-rich conditions in modern Lake Taupo.…”
Section: Changes In Apparent Length Of Diatom Filamentssupporting
confidence: 74%
“…In the modern Lake Taupo sediment, this ratio is 16.7, suggesting relatively long filaments of about 17 cells (Table 2). This is analogous to the warm season filament length (11-17 cells) documented by Poister et al (2012) in a Wisconsin lake. Long filaments suggest relatively calm waters and nutrient-rich conditions in modern Lake Taupo.…”
Section: Changes In Apparent Length Of Diatom Filamentssupporting
confidence: 74%
“…In reservoirs of central China, A. ambigua was also reported to grow rapidly with the declining temperatures in early winter, to reach its maximum abundance at a temperature of ~10°C in mid-December, remaining abundant until mid-February (Zhang et al, 2019). Outside China, many studies report that A. ambigua can be very abundant in temperate or high-latitude lakes (Holland, 1968;Dean et al, 1984;Bradbury, 1988;Siver and Kling, 1997;Kauppila et al, 2002;Poister et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Aulacoseira ambigua is characterized by high TP optimum (Barinova et al, 2006). Batch culture experiments indicated that increased phosphorus availability contributed to the seasonal increase in Aulacoseira ambigua filament length and abundance (Poister et al, 2012). Shift of the TP:TN ratio could result in the replacement of diatom communities with Aulacoseira ambigua to the assemblages with Puncticulata radiosa.…”
Section: Discussionmentioning
confidence: 99%